2017
DOI: 10.1112/topo.12001
|View full text |Cite
|
Sign up to set email alerts
|

The Alexander module, Seifert forms, and categorification

Abstract: Abstract. We show that bordered Floer homology provides a categorification of a TQFT described by Donaldson [Don99]. This, in turn, leads to a proof that both the Alexander module of a knot and the Seifert form are completely determined by Heegaard Floer theory.Dedicated to the memory of Tim Cochran and Geoff Mess.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We will not need the above gradings in this paper, but only a simpler grading by Z/2. Gradings by Z/2 on bordered Floer homology have appeared in [Pet18,Pet14,HLW17]. We lay out definitions here directly, specializing to the case of torus boundary, and encourage the reader to compare with earlier literature.…”
Section: Be the Left Typementioning
confidence: 99%
“…We will not need the above gradings in this paper, but only a simpler grading by Z/2. Gradings by Z/2 on bordered Floer homology have appeared in [Pet18,Pet14,HLW17]. We lay out definitions here directly, specializing to the case of torus boundary, and encourage the reader to compare with earlier literature.…”
Section: Be the Left Typementioning
confidence: 99%
“…start by reviewing the relative Z 2 -grading gr on CF . The details are in [22,8]. Let H = (Σ g , α, β, z) be a Heegaard diagram for a closed 3-manifold Y .…”
Section: Proof Of Theorem 12mentioning
confidence: 99%
“…gr induces a relative Z 2 -grading on HF (H), which we also call gr. With respect to both relative There's an analogous story for the bordered invariants CFA and CFD, due to Hom, Lidman, and Watson in [8]. To explain this, we'll need the notion of a bordered partial permutation.…”
Section: Proof Of Theorem 12mentioning
confidence: 99%
“…Other related invariants, for example the determinant and Arf invariant, are consequently determined. Moreover, Hom et al have shown that both the Alexander module of a knot and the Seifert form are determined by Heegaard Floer theory [8].…”
Section: Introductionmentioning
confidence: 99%